2011
DOI: 10.1258/hsmr.2011.011012
|View full text |Cite
|
Sign up to set email alerts
|

Empowering health-care managers in Australia: an action learning approach

Abstract: This paper reports on a training programme using action learning sets designed to enhance the management abilities of health-care managers. Numerous independent reports in Australia, and around the world, have related the lack of management systems and processes to substandard health-care delivery. This has suggested a need for better approaches to the education, training and ongoing development of health-care managers, and this paper reports on an action learning approach trialled over a three-year period. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 39 publications
1
32
0
1
Order By: Relevance
“…Psychological research has shown that a lack of control over working conditions leads to a stressed, demotivated workforce which becomes resistant to change (Bandura and Locke 2003;Cooper 2012). Conversely, empowering employees by giving them more control over their work has been shown to be an effective way of combating stress and a means of achieving lasting change (Savery and Luks 2001;Bandura and Locke 2003;Leggat et al 2011). …”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Psychological research has shown that a lack of control over working conditions leads to a stressed, demotivated workforce which becomes resistant to change (Bandura and Locke 2003;Cooper 2012). Conversely, empowering employees by giving them more control over their work has been shown to be an effective way of combating stress and a means of achieving lasting change (Savery and Luks 2001;Bandura and Locke 2003;Leggat et al 2011). …”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…There is now a strong body of literature establishing that senior managers in acute care health services have responsibility for, and play a pivotal role in, ensuring the success of quality and safety programs [16][17][18][19]. This study addressed a gap in the literature by exploring the views of senior managers on current and future strategies to improve hand hygiene compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The health care system is complex and multidisciplinary, comprising senior executive personnel, clinicians, technical, support/service staff and administrators. Senior hospital managers are those clinical and nonclinical staff with delineated formal responsibility for administrating health care services and divisions, are involved in executive decision-making regarding budgets and staffing, and have responsibility for dealing with the outcomes of adverse events and for implementing systems level change [16][17][18]. As senior health care managers play an important role in patient safety and having input into the design and operationalization of quality improvement programs they can offer a unique perspective on how to improve areas of practice with which healthcare organizations are often struggling to improve [19].…”
mentioning
confidence: 99%
“…This has been shown in especially community-level programmes to develop local capacity and increase sustainability chances [12]. The use of this approach to address system-level challenges in the health sector is increasingly gaining popularity, although it still remains rare [1416]. …”
Section: Introductionmentioning
confidence: 99%